Advances in allograft monitoring after intestinal transplantation. Issue 2 (April 2016) - Lauro, Augusto; Marino, Ignazio R.; Matsumoto, Cal S.
Abstract : Purpose of review: The intestinal allograft, with an enormous lymphoid load, is a highly immunogenic organ which elicits a strong alloimmune response. In the early posttransplant period, a robust graft biopsy protocol via a temporary ileostomy is utilized for surveillance to detect rejection. In the later posttransplant period, after enteral continuity is reestablished, graft biopsies via a colonoscopy become more cumbersome. Alternative methods for intestinal allograft monitoring other than graft biopsy are of particular interest. Recent findings: Biomarkers and diagnostic tools, such as granzyme B, perforin, fecal calprotectin, citrulline, donor-specific antibody, and zoom video endoscopy have all been studied for application as reliable methods of performing intestinal allograft surveillance. Each modality has the capability to monitor a separate and unique process in the host-allograft immune response. Summary: The goal to find a reliable, reproducible, and noninvasive method for intestinal graft monitoring remains an elusive one. Many of the current modalities available only serve to act as complementary tests in conjunction with astute clinical observations. Graft biopsy remains the gold standard for monitoring the intestinal allograft.